The association of gender role attitudes and offense type with public punitiveness toward male and female offenders - Tuncer, Ayşe E. (International journal of law, crime and justice, 2018)
In recent decades, the increase in the prison population around the world has brought a rise in punitiveness toward offenders intofocus. With a six-fold increase since the 1970s, the United States has the highest incarceration rate with almost one out of every 100 inhabitants in prison (Walmsley, 2013). The inception of “tough on crime” policies in the United States influenced other Anglo-Saxon jurisdictions such as Australia, New Zealand and the United Kingdom. Similar developments can be observed in a number of Continental European countries (Roberts and Indermaur, 2007). For instance, according to the European Sourcebook of Crime and Criminal Justice Statistics (Aebi et al., 2014), the prison population in the Netherlands grew five-fold from the 1970s to 2011. During the same period, Spain has witnessed an almost quadrupled rate from 40 to 156 inmates per 100,000 inhabitants.